Modeling the fiscal sector of the Nigerian economy - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2013)
The model examines the effect of fiscal policy shocks on macroeconomic variables and the response of fiscal policy variables to oil price and capital expenditure shocks.
Includes bibliographical references.
oif 07/03/17
Loans
Keywords: Fiscal policy; Macroeconomic modeling; Economic modeling; Economic forecasting; Macroeconomics; Nigeria